Control de un sistema integrado en cascada con un calderín alimentador de vapor constante a un reactor para la producción de cloruro de aluminio virtualizado usando una estrategia de control predictivo basado en modelos MPC. - Amores Molina, Daniel David (2022)
This research work models, virtualizes and controls an integrated cascade system for the production of aluminum chloride, based on the implementation of a boiler, which aims to produce constant steam at a certain temperature, the same that is coupled to the jacket of a continuous stirred reactor, which aims to produce aluminum chloride by the entry of hydrochloric acid inside which is deposited aluminum. Once the two processes are coupled, control strategies are designed based on traditional PID algorithms, one to control the steam temperature at the boiler outlet, and the other to control the aluminum chloride concentration at the reactor outlet. In addition, a model-based predictive control (MPC) algorithm is designed, with four control objectives: the first one is to bring the steam temperature to the desired value, which in turn indirectly controls the internal temperature in the reactor; the second one controls the concentration error; the third and fourth ones guarantee that the variations of the control actions are minimal, thus preserving the useful life of the actuators.